Comparative studies of Eragrostis plana (annonigrass) and lowland native pasture in the area of Santa Maria, Rio Grande do Sul, Brazil. II. Cumulative growth curve and regrowth - Hall, George A.B.; Nascimento, Agenor do (Pesquisa Agropecuaria Brasileira, 2014)
Eragrostis plana (Nees) and lowland native pasture in the Santa Maria area, Rio Grande do Sul, Brazil, were compared with regard to cumulative growth and height, and 90-day regrowth. Twenty-four plots measuring 12 m2 were used for each pasture, distributed in two blocks of 12 plots each to 12 monthly cuttings during an experimental period of one year. The trial began 30 days following mewing en 08/30/74. Cumulative dry matter and crude protein production increased as the trial progressed, with the largest productions occuring from October to January, while cumulative growth in the first two months, and from January on, were small. E. plana gave more cumulative dry matter and crude protein production than native pasture during the entire trial (P <0,01). Pasture heights showed similar responses to dry matter production. Mean dry matter and crude protein production during 90-day regrowth showed highly significant effects due to pasture and month (P <001), with the majority of variation being explained by a quadratic regression of month on production. E. plana gave marked increases in regrowth in spring and summer compared to native pasture, but differences were no significant (P <0.05) for 90-day dry matter production in the periods ending in May, June, July, August and September; extremely low productions were noted in these periods. Under normal productive conditions in Rio Grande do Sul, the most critical time of year in terms of feed availability is the winter. Under the conditions of this experiment, E. plana did not show any great advantage over native pasture at this time of year.